2017
DOI: 10.1021/acs.jpcc.7b09592
|View full text |Cite
|
Sign up to set email alerts
|

Distinguishing Thermal and Electronic Effects in Ultrafast Optical Spectroscopy Using Oxide Heterostructures

Abstract: Measuring time-resolved photoexcited properties in semiconductors is critical to the design and improvement of light-harvesting devices. Although ultrafast pump–probe spectroscopy offers a promising route to understand carrier recombination mechanisms and quantify lifetimes, thermal contributions to the transient optical response can be significant and need to be properly accounted for to isolate carrier-induced contributions. We demonstrate the use of broadband ultrafast optical spectroscopy on type I heteros… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
15
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 25 publications
(17 citation statements)
references
References 58 publications
2
15
0
Order By: Relevance
“…The near-IR probe enables interrogation of the near-band edge carriers with an effective detection depth of ~4 [53], which corresponds to ~36 nm near the CZTSe bandgap. In the band gap region, the reflectivity change contains contributions from carrier effects such as band-filling and band gap renormalization and from heating [54][55][56]. This assignment and time scale is consistent with that previously reported for pure sulfide CZTS single crystals [36].…”
Section: Resultssupporting
confidence: 89%
See 1 more Smart Citation
“…The near-IR probe enables interrogation of the near-band edge carriers with an effective detection depth of ~4 [53], which corresponds to ~36 nm near the CZTSe bandgap. In the band gap region, the reflectivity change contains contributions from carrier effects such as band-filling and band gap renormalization and from heating [54][55][56]. This assignment and time scale is consistent with that previously reported for pure sulfide CZTS single crystals [36].…”
Section: Resultssupporting
confidence: 89%
“…Carrier cooling and non-radiative recombination transfer energy to the lattice, which affects the reflectivity both above and below the band gap due to the temperature dependence of the refractive index [58]. Recent work on oxide thin films has illustrated the important, and often dominant, effect of temperature on TR response [56,59]. However, thermal effects do not appear to play a significant role here.…”
Section: Resultsmentioning
confidence: 96%
“…Such contrasting decay characteristics indicate the possibility of different relaxation processes in respective time scales. As demonstrated in several previous studies 36,[38][39][40] , in transient absorption and reflectivity measurements, transient heating of the sample induced by the pump laser pulse can cause thermal components in the measured spectra and a proper assessment and isolation of its components are essential for accurate interpretation of photoinduced (nonthermal) electronic responses. To this end, we estimated the effect of pump-induced heating on TDR signal and concluded that the TDR signal of Y 2 Ti 2 O 5 S 2 probed at 0.24 eV reflects only photoinduced electronic processes as shown in the Supplemental Note 1 (Supplementary Figs.…”
Section: Resultsmentioning
confidence: 95%
“…Therefore, the measured values of α e-e and β e-ph can be considered as the average value contributed by all the metal layers spaced by the dielectric layer. It is also further noticed that this heat energy further broadens the electronic energy bands during the process of lattice cooling, which results in a red-shift in the transient absorption peak positions, [32] which is already evident in Figure 2d.…”
Section: Nonlinear Absorption Dynamics Of Photonic Minibands: Experiments and Simulationsmentioning
confidence: 61%